META ANALISIS TRANSFORMASI DIGITAL TERHADAP KINERJA KARYAWAN: TINJAUAN DARI STUDY TERDAHULU - Ageng Syofy; Nur Azizah; Aaliyah Cahya Mustika; Mailatul Abadiya; Budi S.P.N. (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
This study employs a quantitative meta-synthesis (systematic literature review) focusing on empirical studies that examine the relationship between Digital Transformation (DT) and Employee Performance (KP) using multivariate statistical analysis such as SEM-PLS or regression. The analysis includes explicit statistical parameters such as path coefficients, T-statistics, and P-values from 14 studies (k=14) drawn from various contexts, including PLN UP3 Situbondo, Bank Indonesia Jabar, Moewardi Hospital Surakarta, and Songket Palembang SMEs. The review results consistently show that DT has a positive and significant impact on employee performance across various sectors such as healthcare, banking, and public services. The strength of DT's influence on KP is found to be highly optimistic when mediated by key variables such as Job Satisfaction, Individual Readiness to Change, and Digital Empowerment. Paradoxically, the review finds that Technostress can positively and significantly affect performance, especially when Organizational Support (Perceived Organizational Support) acts as a moderator that strengthens it. The study concludes that the success of digital transformation lies not only in technology adoption but also in human-centric strategies. These findings enrich the human resource management literature by integrating the JD-R model and providing strategic guidance for managers to manage digital stress through organizational support.